Overview of CW electron guns and LCLS-II RF gun performance - Zhou, F.; Adolphsen, C.; Dowell, D.; Xiang, R. (Frontiers in Physics, 2023)
Various continuous-wave (CW) electron gun technologies are reviewed, including DC, superconducting radio frequency RF (SRF), hybrid DC-SRF and normal-conducting RF. Also, the SLAC Linac Coherent Light Source II (LCLS-II) normal-conducting RF gun and injector are described, and the performance to date, including the bunch emittance achieved and the dark current observed, is presented.